Research on magnetic resonance imaging in diagnosis of Alzheimer's disease - Guohua Zhao; Haixia Zhang; Yuzhen Xu; Xiuli Chu (European Journal of Medical Research)
Abstract As a common disease in the elderly, the diagnosis of Alzheimer's disease (AD) is of great significance to the treatment and prognosis of the patients. Studies have found that magnetic resonance imaging plays an important role in the early diagnosis of Alzheimer's disease. This article tries to review the application of magnetic resonance imaging in the diagnosis and differential diagnosis of Alzheimer's disease.